Utilization of eafd in concrete composite - Muhd, F.N. (Trans Tech Publications Ltd, 2017)
Industrial waste products can be considered as renewable resources. Steel industry wastes have a severe impact on the environment whereas this industry involves a myriad of operations which create vast volumes of air emissions, liquid effluents, and solid wastes. This study presents the feasibility of using Electric Arc Furnace Dust (EAFD) as a cement replacement material (CRM) in comparison with silica fume (SF) and fly ash (FA). The EAFD is a complex byproduct material of steel produced by electrical - arc furnace and consisting mostly of metal oxides. The results showed that the workability of the EAFD mixes is comparable to the control mix even when the percentage of the EAFD was increased. On the other hand, as the replacement percentage was increased, the use of FA, SF resulted in higher, lower workability, respectively. Furthermore, the EAFD significantly affected the setting time, where 3 of the EAFD replacement resulted in prolonging setting time reached more than 24 hours, while the use of SF and FA has insignificantly affected the setting time. The 3 of EAFD is found to be the optimum replacement in terms of compressive strength and it has a similar effect to a replacement level of 5 of SF and 15 of FA. © 2017 Trans Tech Publications, Switzerland.